THE ROLE OF INCOME TAX IN INDIA FOR PROMOTING ECONOMIC RESOURCE REDISTRIBUTION: A COMPREHENSIVE ANALYSIS - 1 Minal Ritesh Parekh, 2 Dr. Sharma Rashmi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Income tax, a fundamental component of fiscal policy in most nations, serves a dual purpose: revenue generation and the promotion of economic resource redistribution. This research paper offers an in-depth exploration of income tax's pivotal role in fostering a more equitable distribution of economic resources within a country. It delves into the mechanisms that underpin progressive taxation, examines the tangible impact of income tax policies on income inequality, and scrutinizes the challenges and potential reforms necessary for optimizing income tax systems towards achieving a more just and balanced wealth distribution. Through a thorough analysis of progressive taxation, wealth redistribution mechanisms, and the broader implications of income tax, this paper sheds light on how income tax can be harnessed as a potent instrument for advancing economic resource redistribution goals.